INTERNATIONAL LAW AND IMPERATIVES OF ECONOMIC DIPLOMACY IN THE CONTEXT OF TURBULENCE IN INTERNATIONAL RELATIONS - Flissak, Kostyantyn (Актуальні проблеми правознавства, 2025)
The axiom of the effective functioning of the system of international relations is the priority role of international law with its regulatory and guiding functions in accordance with the accepted legal norms, requirements and framework conditions. The issue of international legal norms is the subject of research and the object of attention of scientists and practitioners from different countries of the world, without exaggeration, since the beginning of the activity and establishing of the mechanism of international law itself. This problem does not lose its relevance in modern conditions. The range of studied areas and segments of the role of international law in a globalized world is extremely wide.Most of the current international legal conditions of our time are formed and, accordingly, operate in the context of globalization. However, the dynamics of global development are undergoing permanent changes, a significant part of which arises on the basis of conflicts of interest. As a result, new phenomena and categories in the system of international relations are on the agenda. At the same time, economic diplomacy remains an effective tool for achieving the necessary compromises, minimizing the negative consequences of globalization and at the same time gaining advantages, as well as providing national interests and strengthening the competitive positions of national firms and companies. This determines the objectivity of focusing on the effectiveness and usefulness of modern international law and its role in levelling turbulent phenomena in international economic relations. At the same time, a special place is seen in the international legal support for the effectiveness of modern economic diplomacy in providing national economic interests.The article considers the features of the modern development of the globalized world in the context of turbulence in international economic relations, its characteristic features and consequences. There is drawn attention to the peculiarities of protecting the country’s national interests in turbulence conditions by forming adequate norms and framework conditions of international law to ensure effective forms of economic diplomacy. Also are considered modern challenges for the system of international law and international economic relations, in particular the phenomenon of alterglobalism and manifestations of economic nationalism. The author draws attention to the need to develop appropriate legal mechanisms and imperatives for protecting one’s own national interests in the context of activating economic nationalism. The emphasis is placed on the need to improve the legal support of the rehabilitation policy by the norms of international law. There is summarized the range of imperatives of economic diplomacy within the framework of international law.Based on the results of the analysis, there are formulated conclusions in the segment of increasing relevance of the international law role in the settlement and levelling of turbulent phenomena in international economic relations and effective legal support for economic diplomacy.